2022
DOI: 10.23919/ien.2022.0002
|View full text |Cite
|
Sign up to set email alerts
|

Milestones, hotspots and trends in the development of electric machines

Abstract: As one of the greatest inventions of human beings, the electric machine (EM) has realized the mutual conversion between electrical energy and mechanical energy, which has essentially led humanity into the age of electrification and greatly promoted the progress and development of human society. This paper will briefly review the development of EMs in the past two centuries, highlighting the historical milestones and investigating the driving force behind it. With the innovation of theory, the progress of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…For example, at small (15 kW) power levels, it is seen that the torque per volume of a DC-VRM operating at 200 r/min is 17.4 kNm/m 3 , which is reasonable when compared to a conventional PMSG operating at 150 r/min, which yielded 24 kNm/m 3 . The predicted torque density of the DC-VRM is because it operates on the flux modulation principle and as such, can provide high torque capability based on magnetic gearing effects [15,16]. Meanwhile, it is observed that the torque ripple of the DC-VRM is 2.5 times that of the PMSG, and this is usually the Achilles' heel of FMMs because of their double-salient design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, at small (15 kW) power levels, it is seen that the torque per volume of a DC-VRM operating at 200 r/min is 17.4 kNm/m 3 , which is reasonable when compared to a conventional PMSG operating at 150 r/min, which yielded 24 kNm/m 3 . The predicted torque density of the DC-VRM is because it operates on the flux modulation principle and as such, can provide high torque capability based on magnetic gearing effects [15,16]. Meanwhile, it is observed that the torque ripple of the DC-VRM is 2.5 times that of the PMSG, and this is usually the Achilles' heel of FMMs because of their double-salient design.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, emerging non-conventional machines such as flux modulation machines (FMMs), which are new and emerging, are currently being investigated for variable-speed wind generator concepts. Their operation is based on the principle of modulated armature static fields that could be paired along with those produced by the field source thanks to inherent rotor gearing effects to yield high-torque density [15,16]. They also exhibit stator-mounted design features that enhance thermal management as well as promote stationary PM or brushless non-PM excitation, respectively [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1950s, Emelyanov and his co-researchers in the Soviet Union were the first to use a variable structure controller. For its efficiency and precision, the variable structure controller (VSC) idea has been widely employed in military and civilian applications, according to a study article by Utkin, as well as subsequent articles [7][8][9][10][11][12]. Zinober [14], Young [13], Spurgeon [15], Slotine and Sastry [16], and Edwards [17] have developed VSC for instability and complex system in Europe and the United States.…”
mentioning
confidence: 99%